PENGGUNAAN MEDIA SOSIAL BERLEBIH DAPAT MENYEBABKAN INSOMNIA PADA REMAJA DI SENTOLO KULON PROGO - sujono riyadi; Nur Fatih Udin (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2020)
Background: Insomnia is a sleep disorder that can interfere with physical, emotional and cognitive growth. One of the causes of insomnia is due to bad habit factors such as a lifestyle that always worships technological sophistication, so that many people often linger in using the internet. The very intense use of social networks can be in the form of Facebook, Instagram, and WhatsApp. This study aims to determine the effect of the duration of social media use on the incidence of insomnia in adolescents at senior high school 1 Sentolo Kulon Progo.Methods: Non-experimental research with correlative quantitative descriptive approach, carried out in a cross-sectional manner. The instrument used a questionnaire. The sample of this study was 58 remaining students of class XI, XII in SMA Negeri 1 Sentolo Kulon Progo using random sampling techniques and analyzed using the Somers'd test.Results: The results of this study obtained a p value of 0.003 (p <0.05), and r = 0.291, there is an influence in the duration of social media use with the incidence of insomnia in adolescents in Senior High School 1 Sentolo Kulon Progo.Conclusions: There is a significant effect between the duration of social media use and insomnia among adolescents in SMA Negeri 1 Sentolo Kulon Progo. Keywords: Duration, Social Media, Insomnia, Adolescents.